Innovation in the bioeconomy: Perspectives of entrepreneurs on relevant framework conditions - Kerstin Wilde; Frans Hermans (Journal of Cleaner Production, 2021)
Although entrepreneurial activities are of key importance in a properly functioning innovation system, the micro level of actors is often neglected in the innovation systems' literature. The goal of this paper is to show how the configuration of innovation systems shapes entrepreneurs' perceptions and behaviors. The originality of the present article rests upon a novel framework that distinguishes between the willingness, capability, and perceived opportunities of entrepreneurs embedded in specific innovation systems. We explore the perceptions of 30 entrepreneurs from two European bioeconomy cluster regions who are engaged in R&D and collaborative experimentation in the chemical, plastics, and construction materials industries. Our findings show that with documented innovation willingness, entrepreneurs' innovation capacity is not the decisive bottleneck. Rather, bioeconomy actors perceive that innovation opportunities are blocked by institutions at the national and international levels. The configuration of relevant sectoral innovation systems and value-chains is crucial. We conclude that bioeconomy promotion should emphasis the demand side and systemic multi-level policies that address innovation barriers with due consideration for industry-specific innovation systems and value-chain configurations.
Keywords: 330; bioeconomy; barriers to innovation; innovation capabilities; innovation opportunities; STI policy; sectoral innovation systems